2016
DOI: 10.3389/fphar.2016.00440
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit and Safety of Aspirin for Primary Prevention of Ischemic Stroke: A Meta-Analysis of Randomized Trials

Abstract: Background: Although aspirin is effective in the secondary prevention of stroke among men and women, its use in primary prevention remains controversial. We conducted a meta-analysis of randomized trials to evaluate the benefit and safety of aspirin for the primary prevention of ischemic stroke.Methods: We searched three electronic databases (Medline, the Cochrane Central Register of Controlled Trials, and Embase) for articles published before August 1st, 2016. Randomized trials reporting the effect of aspirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
1
21
0
2
Order By: Relevance
“…11 Regarding cardiovascular disease, the most favorable impact could be noticed for MACE, with most meta-analyses 14,16,17,19 (but not the study of the ASPREE Investigator Group), 12 reporting a decreased risk in people receiving aspirin. However, this apparent benefit does not translate into tangible benefits on reducing the risk of cardiovascular mortality, 12,15,17,19 or ischemic stroke, 12,15,17,19 which appears constantly unaffected by the use of aspirin in all published studies, except in the meta-analysis of Lei et al 18 A modest favorable effect of aspirin in decreasing the risk of myocardial infarction was noted in two meta-analyses, 15,17 but not in other two meta-analyses, 14,19 nor in the randomized trial of the ASPREE Investigator Group. 12 The potential impact of aspirin on future cancer risk also appears largely heterogeneous, wherein one meta-analysis reported a lower risk, 25 other meta-analyses failed to report a significant effect, 16,22,23 while the randomized trial of the ASPREE Investigator Group even reported a 31% increased risk of developing malignancies, especially colorectal cancer (►Table 2).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…11 Regarding cardiovascular disease, the most favorable impact could be noticed for MACE, with most meta-analyses 14,16,17,19 (but not the study of the ASPREE Investigator Group), 12 reporting a decreased risk in people receiving aspirin. However, this apparent benefit does not translate into tangible benefits on reducing the risk of cardiovascular mortality, 12,15,17,19 or ischemic stroke, 12,15,17,19 which appears constantly unaffected by the use of aspirin in all published studies, except in the meta-analysis of Lei et al 18 A modest favorable effect of aspirin in decreasing the risk of myocardial infarction was noted in two meta-analyses, 15,17 but not in other two meta-analyses, 14,19 nor in the randomized trial of the ASPREE Investigator Group. 12 The potential impact of aspirin on future cancer risk also appears largely heterogeneous, wherein one meta-analysis reported a lower risk, 25 other meta-analyses failed to report a significant effect, 16,22,23 while the randomized trial of the ASPREE Investigator Group even reported a 31% increased risk of developing malignancies, especially colorectal cancer (►Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…16,22,23 Unlike these endpoints, the bleeding risk of patients receiving aspirin for primary prevention of cardiovascular disease was found to be consistently increased in all published studies. 12,14,17,22 In only one meta-analysis was aspirin treatment not associated with intracranial bleeding, 22 whereas such risk was found to be significantly increased in the remaining reports, 14,17,18 as well as in the randomized trial of the ASPREE Investigator Group. 12 Regarding aspirin dosages, no major benefits (or harms) could be observed in studies analyzing the effect of low-dose aspirin (►Table 3).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…To further complicate matters, one has to consider the risks associated with aspirin used as primary prevention of cerebrovascular disease, e.g. the increased risk of cerebral bleeding which may outweigh benefits of reduction in ischemic stroke [20].…”
mentioning
confidence: 99%